PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN MODERASI BERAGAMA - Ice wirevenska Ice wirevenska (Lembaga Sepercenter, 2025)
Islamic Religious Education (IRE) plays a strategic role in building religious moderation, especially amid the challenges of globalisation and the rise of intolerance. Religious moderation emphasises balance in understanding religious teachings, avoiding extremism, and fostering tolerance and inclusivity. This article aims to examine the contribution of PAI in shaping the moderate character of the younger generation through the curriculum, learning methods, and the role of teachers as role models. The research method used is library research with a qualitative approach. The results of the study show that PAI can be an effective instrument for internalising the value of moderation, if supported by a contextual curriculum, dialogic learning methods, and the active role of educators in guiding students. In conclusion, PAI not only functions as a medium for transferring religious knowledge, but also as a strategic tool in building a tolerant, inclusive, and civilised society.